Educational journalism in Ukraine (results of content analysis) - Petro Katerynych (Синопсис: текст, контекст, медіа, 2021)
The article describes theoretical approaches to understanding educational journalism, characterizes the concepts of educational journalism in the Ukrainian and global media space, and builds a model of influence of external factors on the coverage of education issues in the mass media outlets. The tasks of the research are: 1) to study theoretical developments and approaches to the functioning of educational journalism in the media environment; 2) to trace the genre and thematic features of the analyzed educational media outlets (on the example of “Pedpresa”, “Osvita.ua”, “New Ukrainian School”, “Osvitoria”). The research methodology is content analysis of specialized media on educational topics. These media have a regular infill of multigenre and multithematic content of educational topics, actively use tools to create a multimedia content, have a high traffic in the segment of online media educational profile (according to the service statistics “Similar Web”). It was found among the analyzed content of the four online media of educational specialization (3,352 publications) that by the genre structure notes prevail (2,714; 80.9%), there is a lack of reportage (56; 1.7%) and interviews (130; 3.9%). The low number of analytical genres is especially noticeable with regard to the topics of preschool, inclusive and vocational education. A content analysis in Group 1 (2,366 materials, 70.6% of the total sample in the two groups) showed that the largest number of materials during the analyzed period concerned the topics of primary and secondary education (1,131 materials, 47.8%), and the smallest number concerned vocational education (131, 5.5%). Analysis of materials in the Group 2 (29.4% of the materials considered in both groups) showed that the topic of primary education prevails (401 materials, 40.7%), the share of materials relating to distance education is significant (16.7% in “NUS” and 16.9% in “Osvitoria”). Most of the materials of the media “PedPresa” (83%), as well as a significant part of “Osvita.ua” (63%) are borrowed or supplemented by the material from the sites of the MESU, UCEQA or other sources. These results determine the practical value of the study.